Geochemistry and Mineral Resources - Saleh, Hosam M.; Hassan, Amal I. (IntechOpen, 2022)
Geochemistry is crucial in understanding and controlling environmental concerns. The effects of global warming are also being monitored through geochemical measurements in the atmosphere and oceans. Increasingly sensitive instrumentation enables continuous monitoring of pollution levels in the air, water, and on land, allowing high-quality data to support and enforce environmental regulations governing emissions. As a result, geochemistry has become an essential part of scientific and political discussion on many environmental challenges. Improving our knowledge of life on Earth may be the most essential job done by geochemists. This book includes a variety of data relevant to geochemistry and highlights research related to mineral wealth and mining and the development of strategies and scientific standards to significantly increase oil exploitation in the long term. It also provides information on the effects of geochemical components on humans and the environment, as well as environmental and geochemical exploration surveys through sediments.